Neanderthals and the cult of the Sun Bird. (1st August 2019) - Finlayson, Stewart; Finlayson, Geraldine; Guzman, Francisco Giles; Finlayson, Clive
Abstract: The Golden Eagle has played a prominent part in the cultures and traditions of people across Eurasia and North America. The Neanderthals have for a long time been considered incapable of systematically catching birds of any description. Recent work has demonstrated that not only were they able to catch birds, they also took diurnal raptors. In this paper we show that Neanderthals selectively took the largest raptors at their disposal within Eurasia. Among these large raptors was the Golden Eagle, the most powerful and dominant of the raptors. Neanderthals and Golden Eagles co-shared the same habitats and landscapes across the Palaearctic region. We show that the long human/Golden Eagle association goes at least as far back as the Neanderthals. Highlights: The Golden Eagle was the most frequently caught raptor by Neanderthals. Golden Eagles were caught for their feathers and talons. Golden Eagles were probably ambushed by Neanderthals at carcases. The tradition of catching raptors dates to at least 130kya. Neanderthals are the first humans known to practice eagle-catching.